Cyber sexual harassment: a cross-sectional survey over female university students in Upper Egypt - Arafa, Ahmed E.; Elbahrawe, Rasha S.; Saber, Nahed M.; Ahmed, Safaa S.; Abbas, Ahmed M. (International Journal Of Community Medicine And Public Health, 2017)
Background: The striking rise in the internet users has resulted into high potential for abuse. Cyber sexual harassment is a type of internet abuse that carries many negative emotional consequences and could undermine the mentality of young people. The objective of this study is to investigate the rates of exposure to cyber sexual harassment among female students in Beni-Suef University and explore the correlating factors. Methods: A total of 2350 female students representing all academic years of all faculties of Beni-Suef University were recruited to participate in this cross-sectional study. An Arabic language self-administered questionnaire was designed and comprised three sections; socio-demographic characteristics, exposure to cyber sexual harassment in the past 6 months, and emotional effects of exposure. Results: Almost 80% of all the surveyed female students reported experiencing cyber sexual harassment during the past 6 months, and most of the victims were exposed to cyber sexual harassment more than once. Students living in urban areas and students who spent more hours per day using the internet reported more exposure (p<0.05). The harassed students responded mostly by anger (65%), fear (20.1%), hatred (18.5%) and sorrow (18.4%) towards the harassment incidents. Conclusions: Female students in Beni-Suef University are highly vulnerable to cyber sexual harassment, which is shockingly prevalent. Administrations in Beni-Suef University, as well as other Egyptian Universities, should adopt anti-cyber sexual harassment programs. Such programs have to introduce overwhelming policies and regulations that counter fight cyber sexual harassment. Such policies can be used as guidance for the university students, their families and their academic staff.